A simple method for calculating the stress intensity factors for complex 3D cracks at a notch. (June 2016) - Peng, D.; Jones, R.
Abstract: When performing a safety/durability assessment of structural components it is often necessary to consider both fatigue crack propagation and failure by fast fracture among the possible modes of failure. In this context the stress intensity factors at crack tips are important parameters for estimating residual life and criticality. The purpose of this paper is to present a simple method for calculating the mode I stress intensity factors ( K ) for through-the-thickness flaws with an oblique (part) elliptical crack front. A range of examples are presented to demonstrate the accuracy of this method.